2018
DOI: 10.1111/cpf.12538
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of physical activity from Actigraph GT3X+ accelerometers worn on the dominant and non‐dominant wrist

Abstract: The purpose of this study was to evaluate the agreement between several activity measures using raw acceleration data from accelerometers worn concurrently on the dominant and non-dominant wrist. Fifty-five adults (31·9 ± 9·7 years, 26 males) wore two ActiGraph GT3X+ monitors continuously for 1 day, one on their non-dominant wrist and the other on their dominant wrist. Paired t-tests were undertaken with sequential Holm-Bonferroni corrections to compare wear time, moderate-vigorous physical activity (MVPA), ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
3
13
1
Order By: Relevance
“…For instance, in [23] the authors found no significant difference between wrists’ accelerations. Similar results were presented in [24], however both studies investigated cohorts of young adults (mean age was approximately 32 and 22 years, respectively). The preceding research on an older sample (mean age was approximately 49 years [25]) and a more exhaustive study on hand-dependent accelerations of AREA participants [26] suggest that the difference between hand use might be related to age, and therefore this requires further examination.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, in [23] the authors found no significant difference between wrists’ accelerations. Similar results were presented in [24], however both studies investigated cohorts of young adults (mean age was approximately 32 and 22 years, respectively). The preceding research on an older sample (mean age was approximately 49 years [25]) and a more exhaustive study on hand-dependent accelerations of AREA participants [26] suggest that the difference between hand use might be related to age, and therefore this requires further examination.…”
Section: Discussionsupporting
confidence: 81%
“…The agreement of non-dominant and dominant limbs as well as of correct vs. erroneous hip placements was high. The lack of difference between non-dominant and dominant wrist is well supported by previous research [ 40 , 41 ], although some studies found statistically significant differences between both sides [ 36 ]. A recent study in older adults found incorrect accelerometer placements in more than 15% of the participants for one or more days during a seven day measurement period [ 42 ], emphasizing the importance of including erroneous placements in validation studies.…”
Section: Discussionsupporting
confidence: 69%
“…All monitors were worn on the right side for the duration of data collection, as shown in Figure 1 . Of note, Buchan et al [ 37 ] and Dieu et al [ 38 ] demonstrated strong agreement between accelerometer data collected on the dominant and nondominant sides. Accelerometers were initialized simultaneously and programmed to collect data at 100 Hz.…”
Section: Methodsmentioning
confidence: 92%